Management of Human Talent and quality of service at the National University of Moquegua -Peru - Gallegos Arapa, Diana (2024)
The position was to prove that there is direct and significant agreement between Human Talent Management (GTH) and Service Quality at the National University of Moquegua (UNAM). In this regard, it is a basic research, at a relational level, with a non-experimental design, with a sample of 170 respondents. The results demonstrate in their variable dimensions: At the 0.000% level of significance, there is positive and moderate agreement between Knowledge and Service Quality with r = 56.7%.; There is positive and high agreement between skills and service quality with r= 69.90% and Attitudes and Service Quality with r= 69.70%. It is concluded that there is a direct and significant relationship between Human Talent Management (GTH) and Service Quality at the National University of Moquegua (UNAM), locating a Rho Spearman of 72.8%. This confirms that the greater the development of the human talent of teachers and other staff, the greater the quality of service appreciated by students.